Impact of antenatal care on neonatal mortality among neonates in Ethiopia: a systematic review and meta-analysis - Tadesse Tolossa; Ginenus Fekadu; Belayneh Mengist; Diriba Mulisa; Getahun Fetensa; Daniel Bekele (BMC, 2020)
Abstract Background As compared to other regions of the world, Sub Saharan Africa (SSA) is the region with the highest neonatal mortality and is the region showing the least progress in the reduction of newborn death. Despite better progress made in reducing neonatal mortality, Ethiopia contributes the highest rate of neonatal death in Africa. In Ethiopia, findings from few studies were inconsistent and there is a need to systematically pool existing data to determine the impact of antenatal care on neonatal mortality among mother-neonate pairs in Ethiopia. Methods Published articles from various electronic databases such as Medline, Hinari, Pub Med, Cochrane library, the Web of Science, and Google Scholar were accessed. Also, unpublished studies from library catalogs were identified. All observational studies that were conducted on the association between antenatal care follow-up and neonatal mortality among neonates in Ethiopia were included. Data were extracted on the Microsoft Excel spreadsheet and analyzed using STATA 14.1 version. A random-effects model was used to estimate the pooled estimate with a 95% confidence interval (CI). Forest plots were used to visualize the presence of heterogeneity and estimate the pooled impact on antenatal care on neonatal mortality. The presence of publication bias was assessed by funnel plots and Egger's statistical tests. Results Initially, a total of 345 studies were accessed. Finally, 28 full-text studies were reviewed and fourteen studies fulfilled inclusion criteria and included in the final meta-analysis. The overall pooled estimate indicates the odds of neonatal death among neonates from women with antenatal care were 65% lower than those neonates from women who had no antenatal care follow-up (OR: 0.35, 95% CI: 0.24, 0.51). Conclusions In this systematic review and meta-analysis, lack of ANC follow-up increase the probability of neonatal mortality as compared to having ANC follow-up. Thus, we will recommend for more coverages of appropriate antenatal care where risk groups can best be identified and managed.